Size-related seed use by rodents on early recruitment of Quercus serrata in a subtropical island forest - Zeng, Di; Galetti, Mauro [UNESP]; Liu, Juan; Jin, Tinghao; Zhao, Yuhao; Ding, Ping (Elsevier, 2022)
Rodents are ubiquitous seed predators in nature and their size-related seed choice plays an important role in the plant's community structure. However, to understand how size-related seed predation by rodents affects plant recruitment, it is fundamental to predict seed and seedling response to rodent predation. We assessed the interactive effects between seed size and rodent exclusion on seed germination and early seedling survival of Quercus serrata in 10 subtropical forested islands in Thousand Island Lake, China. We found that rodent exclusion significantly improved the proportion of seed germination but not for early seedling survival. The proportion of seed germination in rodent-accessed plots was lower than rodent-exclosure plots and such reduction was strengthened by seed size. The proportion of early seedling survival was similar in both treatments and both increased with seed size. Our study found a significant size-related seed choice by rodents at the seed germination stage and showed that seeds would experience conflicting selective pressures across life stages in the early recruitment. Our findings highlight that size-dependent seed use by rodents is a key biotic factor to limit the oak early recruitment.
Keywords: Oak early recruitment; Rodent exclusion; Seed germination; Seed-sowing experiments; Seedling survival; Size-related seed consumption